Mounting an effective socio-ecological response to non-communicable diseases in Africa's cities. Issue 1 (2nd January 2022) - Mogo, Ebele R. I.; Lerno, Anthony; Abdeta, Chalchisa; Olufemi, Omotola
ABSTRACT: The burden of non-communicable diseases (NCDs) is rising rapidly in low-middle income countries. Poorly planned urbanization exponentially increases the burden of behavioral risk factors for NCDs. Contexts where people live, work, play and pray are not conducive to wellbeing, particularly the healthy behaviours people are often encouraged to adopt. An ecological framing of solutions is therefore needed to reduce non-communicable diseases across Africa. If the status quo continues, it will practically be impossible to cope with the continuing rise of NCDs on the continent. Health development in Africa must be proactive in addressing the externalities resulting from poorly planned urbanization. This commentary outlines opportunities for promoting health and wellbeing at multiple entry-points, for a robust response to NCDs. We recommend that a holistic lens continue to shape thinking, partnership-building, funding, and incentivizing action toward addressing NCDs in Africa.